The Role of Reflective Journal in Explanatory Text Writing - Dina Ramadhanti; Diyan Permata Yanda (IJECA (International Journal of Education and Curriculum Application), 2024)
Reflective journals are used as self-reflection tool to improve the quality of learning. Students can record their learning process through reflective journals so that they can find out their strengths and weaknesses while studying and are able to choose the right strategy to improve their learning, especially in learning to write explanatory texts. This study aims to describe the role of reflective journals in monitoring the writing process of explanatory text. This type of research is quantitative research using correlational methods. A total of 63 students were randomly selected to work on writing tasks which were monitored using reflective journals. Their responses indicated that reflective journals influenced their motivation, self-confidence, and improved learning. They feel the value and comfort of using a reflective journal while completing writing assignments. This result is directly proportional to the statistical test performed. By using the product-moment correlation test, it shows that the relationship between the reflective journal variable and the ability to write explanatory text is significant and very strong based on the correlation value, namely: 0.828. The use of reflective journals affects the ability to write explanatory texts by 68.6% and the remaining 31.4% is influenced by other variables. These results indicate that reflective journals play a very important role in monitoring the writing process. The role of reflective journals in writing, namely: as a means of self-reflection, a guide as well as a means of recording writing experiences; as a tool to cultivate metacognition and cover up weaknesses in writing; as a tool to increase awareness about cognition, tasks, and self in writing; as a guideline for using the right strategy in writing because they know their strengths and weaknesses in writing; as a tool to organize learning in an effort to complete writing assignments; and as a tool that forms a habit of writing, starting from planning, setting goals, and proper strategies for completing tasks.